A pathogenetic base for the surgical treatment of patients with the transverse-flat deformity of the forefoot - Yaremenko, Dmytro (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
Results of the examination of 401 patients (91.3 % of them were females) with the transverse-flat deformity of the forefoot served as the material for this work. Оnly 10.9 % had a combination of the transverse-flat deformity of the forefoot with some flattening of the longitudinal arch. Proceeding from the anatomic-biomechanical changes and functional disorders, 5 types and 4 degrees of the above deformity were differentiated. In this connection, a technique for the surgical treatment of patients with flattening of the forefoot was devised and grounded.